Cervical cytology, HPV DNA and mRNA–a comparative studyi n 162 patients - Martins, Toni Ricardo; Fedrizzi, Edison N.; Alves, Eduardo V.; Vituri, Cidônia de Lourdes; Silva, Rosemeri M.; Bazzo, Maria Luiza (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Introduction: in contrast to the general improvement of the socioeconomic status of the Brazilian population, pathologies that are characteristic of poor health assistance persist. Among those, cervical cancer (CC) is emblematic; it still presents a persistently high incidence. Objective: to compare the performance of cervical cytology to HPV DNA and mRNA detection methods in 162 patients undergoing routine gynecological clinical practice. Methods: a total of 162 patients attended during routine gynecological examination in a private clinic in Florianópolis, Santa Catarina, Brazil, had cervical samples collected and processed for cytopathological and molecular tests, conventional PCR and NASBA. Positive samples positive for HPV DNA were submitted to Type-Specific PCR (TS-HPV PCR). Patients with altered smears were submitted to colposcopy and biopsy. Results: among the 162 samples, 19.8% (32/162) had altered smears, being 4/32 classified as ASC-H, 9/32 as ASC-US, 9/32 as LSIL and 10/32 as HSIL. Biopsies revealed nine cases of CIN I, nine CIN II and one CIN III, while seven were negative for cervical neoplasia. Overall, HPV DNA was detected in 38.3% (62/162) of the samples and HPV E6/E7 mRNA expression was found in 13.6% (22/162). Using TS-HPV PCR, HPV 16 was the most frequent type, found in 8% of the samples (5/62). Considering CIN2+ the gold-standard, cytology had 38.5% of specificity. Sensitivity and specificity of HPV-DNA PCR and NASBA were, respectively, 100% and 60%; 18.7% and 68.7%. Conclusion: mRNA E6/E7 expression was not a highly specific or sensitive marker for prevalent cervical disease while HPV DNA may be used for cervical cancer screening only in conjunction to more specific adjuvant tests.